1998
DOI: 10.1056/nejm199810153391604
|View full text |Cite
|
Sign up to set email alerts
|

Kashin–Beck Osteoarthropathy in Rural Tibet in Relation to Selenium and Iodine Status

Abstract: In areas where severe selenium deficiency is endemic, iodine deficiency is a risk factor for Kashin-Beck disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(208 citation statements)
references
References 25 publications
(20 reference statements)
3
197
2
3
Order By: Relevance
“…The severity of Se de®ciency in the children in this study is comparable to that described in the most Se de®cient areas of Zaire and China (Thilly et al, 1993;Moreno-Reyes et al, 1998). Despite very low serum Se levels, the children in this study showed a rapid and sustained response to the oral iodized oil.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The severity of Se de®ciency in the children in this study is comparable to that described in the most Se de®cient areas of Zaire and China (Thilly et al, 1993;Moreno-Reyes et al, 1998). Despite very low serum Se levels, the children in this study showed a rapid and sustained response to the oral iodized oil.…”
Section: Discussionsupporting
confidence: 78%
“…In these regions, interactions between Se and iodine de®ciency may be important determinants of patterns of disease. In Tibet, where severe Se de®ciency is endemic, iodine de®ciency is a risk factor for Kashin ± Beck disease (Moreno-Reyes et al, 1998). In rural Zaire, combined iodine and Se de®ciency is associated with increased risk for endemic myxoedematous cretinism (Vanderpas et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This sum gives a scale from 0 to 36. This scale is divided into four stages: stage 0, I (1-10), II (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and III (21-36). The bilateral presence of radiological signs was tested for each variable with the κ-test.…”
Section: Methodsmentioning
confidence: 99%
“…Whether the Kashin Beck osteoarthropathy is also caused by selenium deficiency or combined selenium and iodine deficiency is still the topic of scientific controversy. In any event, further pathogenic factors, e. g. mycotoxins, appear to contribute to this peculiar syndrome (Ge and Young, 1993;Moreno-Reyes et al, 1998).…”
Section: Manifest Selenium Deficiencymentioning
confidence: 99%